(untitled) (Journal of Dhaka National Medical College & Hospital, 2024)
Background: Unhealthy cervix can be presented with diverse pathologies like infective, inflammatory, reactive and neoplastic etc. Cervical cancer, having a multifactorial causation, is the second most common cancer in female population. Objective: To colposcopic evaluation of VIA-positive cases and detection of precancerous lesion of cervix for early management. Methods: This prospective, observational study was conducted from October 2021 to March 2023 on 69 women attending at the “Colposcopy Clinic” of Obstetrics and Gynaecology, Department of Dhaka National Medical College, Dhaka. Only VIA positive cases were taken into consideration. It involved history taking, examination of cervix after acetic acid application (VIA), colposcopic assessment and biopsy for histopathological evaluation. Results: Most of the patients (49.28%) were in the age group of 30-39 years. Among all the subjects, the majority (86.96%) was housewives. Colposcopy evaluated 43 cases as CIN (CIN I -33.33 %, CIN II- 15.94%, CIN-III 13.04%) and 2.90% as invasive lesions. Biopsy evaluated 33 cases as CIN (CIN I-18.84% CIN II-17.39%, CIN III- 14.49%) and 1.44% as invasive lesions. The sensitivity and specificity of colposcopy were 87.87 % and 55.55% respectively. This suggests the role of colposcopy in the evaluation of CIN and cervical cancer. Conclusion: Cervical cancer presents as a major cause of morbidity and mortality, especially in developing countries like Bangladesh. In developing countries, the various screening programs are being implemented for its early detection and treatment. It is evident that colposcopy plays a very important role in early diagnosis and treatment of pre invasive and early invasive carcinoma of cervix. So wide use of colposcopy in screening program of Bangladesh can reduce many young women’s morbidity and mortality. J. Dhaka National Med. Coll. Hos. 2024; 30 (02): 23-27